Análisis y valoración del paisaje en las sierras de la Paramera y la Serrota ( Ávila ) - García Quiroga, Fernando; Abad Soria, Jesús (M+A. Revista Electrónica de Medioambiente, 2006)
Landscape scientific researches are getting nowadays more and more important when considering Integral Planning where development and environment are two mayor issues to achieve the balance between nature and society. The place chosen to perform the research, La Paramera and La Serrota Mountains (Avila), forms a natural protected area for different reasons, among them Protected Lanscape. In order to make the research, taking into account the methodology and fundamental aspects which condition on the landscape approach, we aim to make a landscape description and evaluation of a selected area, so it could be used as a base for future researches.